Analysis of Job Satisfaction and Factors Affecting Dentists' Retention in Rural and Remote Areas of Indonesia - Tiara Oktavia Saputri; Ariq Noorkhakim; Harlye Tangkere; Mutma Inna (Faculty of Dentistry, Universitas Trisakti, 2020)
Background: Maldistribution of health workers, including dentists, is a global issue faced by not only poor and developing countries but also developed countries due to the mobility of health workers, who prefer working in urban areas. The World Health Organization (2012) released global policy recommendations that cover education, regulation, incentives, and personal and professional support to overcome this issue. However, they have not been able to completely solve the issue, as is shown by a description of Indonesia’s Health Profile (2018), which highlights that 43.53% of public health center lack of dentists. The number of studies concerning the real condition experienced by dentists working in rural and remote areas of Indonesia is still limited. Objectives: To analyze job satisfaction and factors affecting dentists’ retention in rural and remote areas of Indonesia. Methods: This study used questionnaire to collect data which was designed based on seven major themes and inserted in Google Form. The link was distributed to dentists who work in rural and remote areas of Indonesia. The sample was selected based on random sampling techniques. Result: The study showed that 45.90% of respondents were not satisfied working in rural and remote areas. Most of the respondents claimed that working conditions, incentives, career and professional development, living conditions, and personal characteristics influenced their interest in working permanently in remote and rural areas. However, political and cultural factors did not give a high impact. Conclusion: The description of job satisfaction and factors affecting dentists’ retention in rural and remote areas of Indonesia is expected to have a positive impact on formulating policy regarding dentists’ maldistribution.